Gene regulation : a eukaryotic perspective - Latchman, David S (Taylor & Francis, 2005)
Gene regulation is an essential process in the development and maintenance of a healthy body, and as such, is a central focus in both basic science and medical research. Gene Regulation, Fifth Edition provides the student and researcher with a clear, up-to-date description of gene regulation in eukaryotes, distilling the vast and complex primary literature into a concise overview.
Advanced text
Keywords: eukaryotické buňky; genetika, lékařská genetika; regulace genové exprese; Gene Expression Regulation; RNA; cytologie, klinická cytologie; Eukaryotic Cells